Internal exile in Fascist Italy : history and representations of confino - Garofalo, Piero; Leake, Elizabeth; Renga, Dana, 1971- (Manchester University Press, 2019)
This book is an accessible history of internal exile's origins and practices under Fascism and of its representation in film, literature and memoir.